Wyndham Lewis's cultural criticism : and the infrastructures of patronage - O'Donnell, Nathan (Liverpool scholarship online., 2020)
This is the first book-length study of Wyndham Lewis's cultural criticism, a valuable body of writing which posed questions that have yet to be answered about the role and status of the artist in a professionalised society, and ultimately about the value (economic, civic, political) of the work of art.